Inclusive Financial Empowerment for MSMEs: Strengthening Capacity for Sustainable Growth through Digital Financial Literacy and Financing - Nusa Perdana, Petrolis; Ngirfan, Achmad; Wida Rahmayani, Melia; Heryah, N.; Wahyudin Zarkasyi, M.; Winarningsih, Srihadi; Sukmadilaga, Citra (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
This community development initiative aimed to enhance Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through increased financial inclusivity and digital financial literacy, addressing challenges in sustainable growth. With a structured approach, the program collaborated with government-backed financial institutions, specifically the Pusat Investasi Pemerintah (PIP) and Pegadaian, to broaden access to tailored financing schemes. Digital financial literacy workshops were conducted to empower MSME, especially in Bandung urban area and rural area across West Java, with the skills to leverage financial technology for effective business management. The methodology encompassed participatory training, counseling, and monitoring to ensure practical knowledge application among 67 MSMEs participants across Bandung. Evaluation showed substantial improvements: 80% of participants secured financing through UMi and Pegadaian’s gold-pawn schemes, and 75% exhibited enhanced proficiency in digital financial tools, resulting in notable business efficiency gains. Despite limitations in digital infrastructure, particularly in rural areas, the program underscored the significance of accessible financial services and digital literacy for MSME resilience. Future recommendations emphasize expanding digital infrastructure, continuous training, and inclusive financing initiatives to foster MSMEs contributions to Indonesia’s economic sustainability.